GAMBARAN TINGKAT DEPRESI PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS PURNAMA PONTIANAK TAHUN 2013 - ., Reren Ramanda (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. Diabetes mellitus (DM)is a group of metabollic diseasethat classified in cronic disease withÂ  characteristic hyperglicemiathat happen because of insulin secretion defect, work of insulin, orboth. The impact of illness and treatment procedures are the stressorthat can cause depression. Objective. The objective of this researchwas to describe the level of depression in patients with DM type 2 inPuskesmas Purnama Pontianak. Method. The method used for theresearch was descriptive survey study. The subjects of this studywere 40 patients with DM type 2 in Puskesmas Purnama Pontianak.Sample taken by consecutive sampling. The qualified sample wasinterviewed with Beck Depression Inventory II (BDI II) for determiningthe level of depression. Result. The result shows that the prevalenceof depression in patients with DM type 2 is 25 %. In details, milddepression is 20 % and moderate depression 5 %. Conclusion.Majority of the depression level in patients with DM type 2 inpuskesmas Purnama Pontianak is mild depression and the dominantcharacteristics in respondent with depression are: age >60, female,married, senior high school graduated, and housewives.Keywords: Diabetes mellitus type 2 (DM type 2), Depression, BeckDepression Inventory II (BDI II)1)Medical School, Faculty of Medicine, Universitas Tanjungpura,Pontianak, West Kalimantan2)Department of Psychiatry, Faculty of Medicine, Universitas Tanjungpura,Pontianak, West Kalimantan3)Department of Health Community, Faculty of Medicine, UniversitasTanjungpura, Pontianak, West Kalimantan